A study on the influences of the Bank Simpanan Nasional total savings deposits / Mayasofa Abdul Bahri - Abdul Bahri, Mayasofa (1997)
With Malaysia enjoying rapid economic growth for the tenth successive year, the man in the street may wonder how much income he or she can save in view of the higher cost of living today. Saving is important, especially if the country has no genuine social welfare system. People are forced to save to prepare for illness, disaster and old age. Bank Simpanan Nasional or BSN as the oldest and the biggest savings institution in Malaysia has a very important responsible to carry out for helping the government to increase domestic savings. This research is conducted not only for the purpose of fulfilling the course requirement but to insist the factors that can influence the growth of total savings deposits in Bank Simpanan Nasional. The identification of those factors, internal and external, will be mentioned in the third chapter. Method to be used in the analysis is the regression model by using Least Square estimation through the Time Series Processors. This is to evaluate the relationship between those factors and the total savings deposits in BSN. Yet, I am kindly hope that the recommendations in the final chapter can help BSN to increase its total saving deposits as well as to achieve their principal objectives.